Atomistic modeling for the extremely low and high temperature-dependent yield strength in a Ni-based single crystal superalloy - Zhang, Z.; Fu, Q.; Wang, J.; Yang, R.; Xiao, P.; Ke, F.; Lu, Chunsheng (2021)
Understanding the temperature-dependent yield strength of Ni-based single crystal superalloys is of great significance for their microstructural design and engineering applications. In this Communication, from an atomistic perspective, the yield strength of a Ni-based single crystal superalloy varying with temperature, especially at extremely low (−272 °C) and high (1227 °C) temperatures, has been investigated. The atomic-scale mechanisms are elaborated by extracting several types of dislocation activities at various temperatures. The anomalous behavior of yield strength dominated by the atomic-scale dislocation evolution is visualized in Ni-based single crystal superalloys.